Pengelolaan Sumber Daya Insani dalam Memasarkan Produk dan Jasa Lembaga Keuangan Syariah - Melis Melis (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2019)
This research discusses the management of human resources in marketing the products and services of Islamic financial institutions. The results of this study prove that Islamic banks and financial institutions in Indonesia are developing very fast. However, the image of banks and Islamic financial institutions in Indonesia is not good. For this reason, several policies in managing Islamic financial institutions need to be addressed. One of them is the aspect of human resources. An employee of a bank and an Islamic financial institution that is accepted must have a good personality, an expert in muqalah fiqh, knowledge of Islamic financial institutions, computers / IT and so on. They must be people who support strongly to practice Islamic economics in their lives.